Antigen Retrieval Immunohistochemistry: Review and Future Prospects in Research and Diagnosis over Two Decades - Shi, Shan-Rong (SAGE Publications, 2011)
As a review for the 20th anniversary of publishing the antigen retrieval (AR) technique in this journal, the authors intend briefly to summarize developments in AR-immunohistochemistry (IHC)–based research and diagnostics, with particular emphasis on current challenges and future research directions. Over the past 20 years, the efforts of many different investigators have coalesced in extending the AR approach to all areas of anatomic pathology diagnosis and research and further have led to AR-based protein extraction techniques and tissue-based proteomics. As a result, formalin-fixed paraffin-embedded (FFPE) archival tissue collections are now seen as a literal treasure of materials for clinical and translational research to an extent unimaginable just two decades ago. Further research in AR-IHC is likely to focus on tissue proteomics, developing a more efficient protocol for protein extraction from FFPE tissue based on the AR principle, and combining the proteomics approach with AR-IHC to establish a practical, sophisticated platform for identifying and using biomarkers in personalized medicine.